Does Chinese OFDI really promote export? - Chih-Fan Lin (China Finance and Economic Review, 2016)
Background: Most papers have come to positive conclusions regarding whether Chinese outward foreign direct investment really promote export. Methods: This paper contributes by correcting model misspecification, wrong variable selection and estimation methods which are prevalent in existing studies and reexamine the relationship between outward foreign direct investment and export trade of China using panel data from 2003 to 2014. Results: The regressions indicate that, on average, the point estimate of the elasticity between Chinese outward foreign direct investment and export trade is at most 0.073, and it is not statistically significant. Sub-sample regressions show that Chinese investment in developed economies slightly substitutes export while investment in developing economies complements export. But these effects disappear when country-specific effects are controlled. Year-by-year regressions show that the complementary effect of OFDI on export is on a steady rise. Conclusions: Using correctly specified model with more appropriate variable selection and estimation methods and take into account the quantitative difference between OFDI and export, any 'substitutionary' or 'complementary' effect is indeed negligible.
Keywords: 330; Outward foreign direct investment; Export; Complementation effect; Substitution effect